Incidence of extra-articular manifestations in ankylosing spondylitis, psoriatic arthritis and undifferentiated spondyloarthritis: results from a national register-based cohort study. (20th November 2020) - Bengtsson, Karin; Forsblad-d'Elia, Helena; Deminger, Anna; Klingberg, Eva; Dehlin, Mats; Exarchou, Sofia; Lindström, Ulf; Askling, Johan; Jacobsson, Lennart T H
Abstract: Objectives: To estimate the incidence and strength of association of extra-articular manifestations [EAMs, here: anterior uveitis (AU), IBD and psoriasis] in patients with AS, undifferentiated SpA (uSpA) and PsA, compared with controls. Methods: Three mutually exclusive cohorts of patients aged 18–69 years with AS ( n = 8517), uSpA ( n = 10 245) and PsA ( n = 22 667) were identified in the Swedish National Patient Register 2001–2015. Age-, sex- and geography-matched controls were identified from the Swedish Population Register. Follow-up began 1 January 2006, or six months after the first SpA diagnosis, whichever occurred later, and ended at the first date of the EAM under study, death, emigration, 70 years of age, and 31 December 2016. Incidence rates (IRs) and incidence rate ratios were calculated for each EAM, and stratified by sex and age. Results: Incidence rate ratios for incident AU, IBD and psoriasis were significantly increased in AS (20.2, 6.2, 2.5), uSpA (13.6, 5.7, 3.8) and PsA (2.5, 2.3, n.a) vs controls. Men with AS and uSpA had significantly higher IRs per 1000 person-years at risk for incident AU than women with AS (IR 15.8 vs 11.2) and uSpA (IR 10.1 vs 6.0), whereas no such sex difference was demonstrated in PsA or for the other EAMs. Conclusions: AU, followed by IBD and psoriasis, is the EAM most strongly associated with AS and uSpA. Among the SpA subtypes, AS and uSpA display a largely similar pattern of EAMs, whereas PsA has a considerably weaker association with AU and IBD.